Better response to Tanreqing injection in frequent acute exacerbation of chronic obstructive pulmonary disease (AECOPD) patients—Real-world evidence from a nationwide registry (ACURE) study - Fan, Guohui; Wang, Dingyi; Wu, Sinan; Li, Demin; Ren, Xiaoxia; Dong, Fen; Huang, Kewu; Chen, Yahong; Zhang, Hongchun; Wang, Chen; Yang, Ting (Frontiers in Pharmacology, 2023)
Objective: Our aim was to systematically investigate the efficacy of Tanreqing (TRQ) injection on in-hospital outcomes among inpatients with frequent or infrequent AECOPD. Methods: In this ongoing, nationwide multicenter registry designed to investigate clinical characteristics, management, and prognoses of Chinese patients admitted for AECOPD in real-world settings, we collected characteristics, comorbidities, in-hospital prognoses, and information on the COPD assessment test (CAT) questionnaire, PEACE questionnaire, and modified British Medical Research Council (mMRC) questionnaire from each enrolled patient. Frequent AECOPD was determined as being admitted to the hospital ≥1 time or visiting the emergency room (ER) ≥ 2 times due to AECOPD within a year. A propensity match method and univariable and multivariable regression models were performed to analyze the efficacy of TRQ on clinical outcomes for inpatients with frequent AECOPD. Results: A total of 4135 inpatients were involved in the analysis, including 868 administered with TRQ and 3267 not administered with TRQ. After propensity score match, among those administered with TRQ, 493 had frequent AECOPD and 358 had infrequent AECOPD. A significant reduction of CAT score at discharge (TRQ median 12, IQR 8.0–16.0; non-TRQ median 13, IQR 9.0–18.0, p = 0.0297), a lower rate of ICU admission (TRQ 0.8% vs. non-TRQ 2.6%, p = 0.0191), and a shorter length of stay (LOS) (TRQ median 11, IQR 9.0–14.0; non-TRQ median 11, IQR 8.0–14.0, p = 0.004) were observed in the TRQ group, compared with the non-TRQ group among frequent AECOPD patients. In the subgroup analysis, for those with a PEACE score >7 on admission, TRQ contributed to a significantly lower CAT score at discharge (p = 0.0084) and a numerically lower ICU admission rate with a marginal statistical significance. Among those with phlegm-heat symptom complex on admission ≥2, a lower CAT score at discharge and a lower ICU admission were also observed in the TRQ group. Conclusion: TRQ injection had better efficacy in patients with frequent AECOPD in reducing ICU admission and alleviating respiratory symptoms, especially for those with higher severity on admission or more phlegm-heat symptoms.